Proposal for an International Carbon Price Floor Among Large Emitters - Parry, Ian.; Black, Simon; Roaf, James (Washington, D.C. : International Monetary Fund, 2021)
Countries are increasingly committing to midcentury 'net-zero' emissions targets under the Paris Agreement, but limiting global warming to 1.5 to 2 degree C requires cutting emissions by a quarter to a half in this decade. Making sufficient progress to stabilizing the climate therefore requires ratcheting up near-term mitigation action but doing so among 195 parties simultaneously is proving challenging. Reinforcing the Paris Agreement with an international carbon price floor (ICPF) could jump-start emissions reductions through substantive policy action, while circumventing emerging pressure for border carbon adjustments. The ICPF has two elements: (1) a small number of key large-emitting countries, and (2) the minimum carbon price each commits to implement. The arrangement can be pragmatically designed to accommodate equity considerations and emissions-equivalent alternatives to carbon pricing. The paper discusses the rationale for an ICPF, considers design issues, compares it with alternative global regimes, and quantifies its impacts.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Climate; Energy; Environmental Economics; Global Warming; Natural Disasters and Their Management